(untitled) (African Human Mobility Review, 2023)
Trafficking in Persons (TIP) is globally widespread. In Africa, however, it is prevalent in West and Central Africa. This paper uses Ghana as a case study to examine efforts that are being made to curb this menace at the national level. Drawing on the concept of institutional collaboration and interviews conducted among key stakeholders and review of policy documents, we found that the major challenges and gaps faced by institutions working to implement mechanisms for cooperation include disparities in definition of terminologies, financial and logistical constraints, underutilisation of online reporting systems, inadequate partner collaborations, a gap in the development of operational guidelines and the drafting of training manuals, operational challenges and high staff turnover. Despite these challenges, we conclude that there has been significant improvement in coordination activities in Ghana among the various institutional actors, led by the Human Trafficking Secretariat. The relevance of this study lies in the fact that it allows for a critical mapping and appreciation of the challenges developing countries face in tackling TIP, which then gives meaning to global northern-prescribed international ranking systems (the tier system) which are otherwise meaningless within the global southern context.